(3YfhGf GdoeQbUGJ hGdoeWQHGJs - (3Ydj Hf ehSi Hf eMeO Hf YHO Gdedc GHf SYjO, GdYfSj GdeOdLj GdeZQHj , CHh GdMSf, fhQ GdOjf,J (B685 (3g` s ((3CMeO Hf jhSa GdCQefGRj s)
(3ChdgG (B:s
(3CeG HYO MeO ddg GdPj TQa GdEfSGf Ydi SGFQ GfhGY GdMjhGf s
(3BNQgG (B:s
(3GdMQjQj(B: (3fbdg Yfg GHf NdcGf aj JGQjNg(B: (3hef CbGe HCQV hgj eLOHI acja jQMd YfgG hGdQHjY CJi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3fSNI QGHYIs
(3HChdgG Jedc eDQN (B1147(3g`s
(3hHgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B249s
Keywords: (3GdCOHs